The Drosophila tumor suppressor vps25 prevents nonautonomous overproliferation by regulating Notch trafficking. - Vaccari, T.; Bilder, D. (Developmental Cell, 2005)
Cell-cell signaling coordinates proliferation of metazoan tissues during development, and its alteration can induce malignant transformation. Endocytosis regulates signaling by controlling the levels and activity of transmembrane receptors, both prior to and following ligand engagement. Here, we identify Vps25, a component of the ESCRT machinery that regulates endocytic sorting of signaling receptors, as an unconventional type of Drosophila tumor suppressor. vps25 mutant cells undergo autonomous neoplastic-like transformation, but they also stimulate nonautonomous cell proliferation. Endocytic trafficking defects in vps25 cells cause endosomal accumulation of the signaling receptor Notch and enhanced Notch signaling. Increased Notch activity leads to ectopic production of the mitogenic JAK-STAT pathway ligand Unpaired, which is secreted from mutant cells to induce overproliferation of the surrounding epithelium. Our data show that defects in endocytic sorting can both transform cells and, through heterotypic signaling, alter the behavior of neighboring wild-type tissue.